DENGUE FEVER WITH WARNING SIGN (CASE REPORT) - Arief Kurniawan,; Rahmat, Rahmat; Roni Darojat Kartapraja, (Journal of Innovation Research and Knowledge, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease infection caused by the dengue virus that enters the circulatory system through the bite of a vector, namely the Aedes aegypti, characterized by plasma leakage. Dengue virus infects endothelium, bone marrow, and Kupffer cells in the liver so that activates the immune system which occurs excessively. Thrombocytopenia occurs due to bone marrow suppression, destruction, and shortening of the life of platelets which interfere with the coagulation system, causing bleeding. We describe a case of a 42-year-old man admitted to the intensive care unit who was diagnosed with dengue fever with a warning sign. In this case, besides complaint of fever, there is also the existence of pain in the pit of the heart, and gums bleeding. During the monitoring process in the room, there are other symptoms such as rash on the skin, nausea, vomiting, persistent heartburn, the difficulty for sleep, also minimal ascites. On laboratory result, hematocrit starts increasing and accompanied with the drop of platelets 50000/mm3 with Ht 49.8%, so that patient is transferred to ICU for monitoring intensively and prevent entering severe dengue. This patient has platelets decrease until reaches 13,000/mm3 and hematocrit reached 48.1% shows the weight clinical that will be experienced patient. The patient who experiences ascites that becomes a predictor will occurrence of DSS so that has a prognosis of dubia. The prognosis for dengue without or with warning signs is generally good.